The choice of embedding media affects image quality, tissue R2* , and susceptibility behaviors in post-mortem brain MR microscopy at 7.0T - Dusek, Petr; Madai, Vince Istvan; Huelnhagen, Till; Bahn, Erik; Matej, Radoslav; Sobesky, Jan; Niendorf, Thoralf; Acosta-Cabronero, Julio; Wuerfel, Jens (Magnetic resonance in medicine, 2019)
PURPOSE: The quality and precision of post-mortem MRI microscopy may vary depending on the embedding medium used. To investigate this, our study evaluated the impact of 5 widely used media on: (1) image quality, (2) contrast of high spatial resolution gradient-echo (T1 and T2* -weighted) MR images, (3) effective transverse relaxation rate (R2* ), and (4) quantitative susceptibility measurements (QSM) of post-mortem brain specimens. METHODS: Five formaldehyde-fixed brain slices were scanned using 7.0T MRI in: (1) formaldehyde solution (formalin), (2) phosphate-buffered saline (PBS), (3) deuterium oxide (D2 O), (4) perfluoropolyether (Galden), and (5) agarose gel. SNR and contrast-to-noise ratii (SNR/CNR) were calculated for cortex/white matter (WM) and basal ganglia/WM regions. In addition, median R2* and QSM values were extracted from caudate nucleus, putamen, globus pallidus, WM, and cortical regions. RESULTS: PBS, Galden, and agarose returned higher SNR/CNR compared to formalin and D2 O. Formalin fixation, and its use as embedding medium for scanning, increased tissue R2* . Imaging with agarose, D2 O, and Galden returned lower R2* values than PBS (and formalin). No major QSM offsets were observed, although spatial variance was increased (with respect to R2* behaviors) for formalin and agarose. CONCLUSIONS: Embedding media affect gradient-echo image quality, R2* , and QSM in differing ways. In this study, PBS embedding was identified as the most stable experimental setup, although by a small margin. Agarose and Galden were preferred to formalin or D2 O embedding. Formalin significantly increased R2* causing noisier data and increased QSM variance.
Keywords: Magnetic Resonance Imaging; kontrastní látky; Tissue Embedding; mozek; formaldehyd; magnetická rezonanční tomografie; Humans; lidé středního věku; mapování mozku; zalévání tkání; Contrast Media; ethery; Ethers; formaldehyde fixation; Autopsy; sefarosa; Aged; Female; pitva; senioři; lidé; počítačové zpracování obrazu; Image Processing, Computer-Assisted; oxid deuteria; poměr signál - šum; Deuterium Oxide; Brain Mapping; quantitative susceptibility mapping; Signal-To-Noise Ratio; post-mortem imaging; ženské pohlaví; Male; Middle Aged; Brain; ex vivo imaging; fosfáty; Sepharose; Specimen Handling; ultra-high field MRI; odběr biologického vzorku; fluorokarbony; mužské pohlaví; Fluorocarbons; Formaldehyde; Phosphates